Atomic Fe Dispersed Hierarchical Mesoporous Fe–N–C Nanostructures for an Efficient Oxygen Reduction Reaction - Zhou, Yu; Yu, Yanan; Ma, Dongsheng; Foucher, Alexandre C; Xiong, Lei; Zhang, Jiahao; Stach, Eric A; Yue, Qin; Kang, Yijin (ACS catalysis, 2021)
Due to the scarcity and high cost of precious metals, the hydrogen economy would ultimately rely on non-platinum-group-metal (non-PGM) catalysts. The non-PGM-catalyzed oxygen reduction reaction, which is the bottleneck for the application of hydrogen fuel cells, is challenging because of the limited activity and durability of non-PGM catalysts. A stabilized single-atom catalyst may be a possible solution to this issue. In this work, we employ a coordination-assisted polymerization assembly strategy to synthesize an atomic Fe and N co-doped ordered mesoporous carbon nanosphere (denoted as meso-Fe–N–C). The meso-Fe–N–C possesses a hierarchical structure with a high surface area of 494.7 m2 g–1 as well as a high dispersion of Fe (2.9 wt %) and abundant N (4.4 wt %). With these beneficial structural properties, the meso-Fe–N–C exhibits excellent activity and durability toward the oxygen reduction reaction, outperforming the state-of-the-art Pt/C electrocatalysts.